Economic growth and environmental sustainability determinants - Bytyqi, Ardita (Logistics, supply chain, sustainability and global challenges, 2024)
Economic growth and environmental sustainability nowadays are considered to be of particular importance, so understanding the main contributing factors is very important as well. This paper aims to examine the common determinants of economic growth and environmental sustainability, inspect the relationship between these key elements, and check their significance in economic growth and environmental sustainability. With data from EU member states for a period of ten years (2011-2020) the panel autoregressive distributed lag technique (ARDL) is used for the aim of this paper. Common determinants such as recycling and environmental taxes were found to be the major contributors to economic growth in the long run. Recycling is found to be a major contributor to environmental sustainability as well, however, environmental taxes are detected to have a negative impact on environmental sustainability in the long run, but none of these determinants have any impact in the short run.
Keywords: ARDL; ARPZ; economic growth; environmental sustainability; gospodarska rast; okoljska trajnost; sustainable development; trajnostni razvoj